High prevalence of Chlamydia trachomatis and Neisseria gonorrhoeae infections in anal and pharyngeal sites among a community-based sample of men who have sex with men and transgender women in Lima, Peru. - Leon, Segundo R (2016)
This study aimed to characterise the epidemiology of Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) infections among men who have sex with men (MSM) and transgender women (TW) in Lima, Peru.